The Labour Contract as a Basis of Appearance of Labour Relations - Вишновецька, Світлана Василівна; Такаджі, Людмила Геннадіївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
The article is devoted to research of labour contract as a basis of appearance of labour relations. The problems of conclusion of labour contract, its entry into force, the time of appearance of the labour relationship are very topical. The labour contract is the main form of realization of the right to work, a basis of appearance of labour relations that makes legal base for their functioning. Before December 28th, 2014 the actual admission to work was a basis of appearance of labour relations between employee and employer. This provision was determined by part 4, article 24 of the Labour Code of Ukraine. Later the article 24 of Labour Code of Ukraine was supplemented, and the actual admission to work was excluded as legal fact of appearance of labour relations. At present only labour contract is a basis of appearance of labour relations, so the legislator clearly expressed its opinion on recognition of the labour contract as consensual agreement. It is important to differ the time of conclusion of the labour contract (an agreement of the parties on its terms) and the time of appearance of labour relations (start of work). Labour relations arise from the day of start of work fixed in the labour contract, and labour contract arise after reaching the agreement between its parties on its terms. The “conclusion of the labour contract” should be distinguished from the procedure of “execution of the labour contract”. Conclusion of the labour contract is a procedure of approval by the parties its terms and form, giving it effective. So, it should be firstly agreed the content and form of the labour contract, and second step is execution of the labour contract. Just execution of the labour contract affects the time of appearance of labour relations. The labour relations appear in the moment of signing the labour contract and issue the appropriate order by the employer. The fact of conclusion of labour contract is a legal fact that is a basis of appearance of labour relations regardless of the labour contract form, which in different extent guarantees the rights and obligations of the parties.